The forms of youth : twentieth-century poetry and adolescence - Burt, Stephanie, 1971- (Columbia University Press, 2007)
"Early in the twentieth century, Americans and other English-speaking nations began to regard adolescence as a separate phase of life. Associated with uncertainty, inwardness, instability, and sexual energy, adolescence acquired its own tastes, habits, subcultures, slang, economic interests, and art forms." "The first comprehensive study of adolescence in twentieth-century poetry, The Forms of Youth recasts the history of how English-speaking cultures began to view this phase of life as a valuable state of consciousness, if not the very essence of a Western identity."--Jacket.